Utilization of Management Information System Applications in Public Services at the Investment and One-Stop Integrated Office of Palopo City - Rosnia; Ibrahim Syah (IECON: International Economics and Business Conference, 2024)
The study explores the implementation of the SiCANTIK management information system to enhance licensing services at the Investment and One-Stop Integrated Office (DPMPTSP) of Palopo City. Using a qualitative descriptive method with a case study approach, data collection involved interviews with employees and users of the application. The findings reveal that SiCANTIK significantly streamlines the business licensing process, allowing the public to submit applications from home without the need to visit the office, thus increasing convenience and reducing time and cost burdens. Additionally, the system offers transparency and clarity in the licensing process, ensuring better service quality. Despite its benefits, challenges remain, including issues with internet network stability, which can hinder application processing, and the problem of incomplete or inaccurate supporting documents submitted by users. To overcome these obstacles, continuous efforts are required, such as improving internet infrastructure and providing socialization or training for users regarding document requirements. Overall, the SiCANTIK application has proven to be an effective tool in enhancing service efficiency, improving data management for employees, and contributing to more accessible and user-friendly licensing services. It demonstrates the potential of digital technology in transforming public service delivery and fostering better governance.